PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH (BKD) KABUPATEN INDRAGIRI HULU - Martha Wijayanti; Rusli Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Labor Productivity in the Civil Service Staffing Agency Indragiri Upstream Region.Productivity can basically be viewed from two dimensions , namely the dimension of individual and organizationaldimensions . Assessment of the productivity problem is not other people see the dimensions of productivity , especiallyin relation to the individual 's personality characteristics . In this context, understanding the essence of productivity is amental attitude that always has the view that quality of life should be better today than yesterday , and tomorrow shouldbe better than today ( Kusnendi , 2003:8 ) . The research was conducted at the Regional Employment Board Indragiri .The purpose of this study was to determine the Civil Servants Work Productivity in Regional Employment BoardIndragiri Hulu . This research uses descriptive qualitative method . Data were obtained from the interview data ,documentary studies , and field observations . Informants in this study were the parties relating to the Employee WorkProductivity using the snowball method . The results showed that Pproduktivitas Civil Servants working in the RegionalEmployment Board Indragiri Hulu is good enough . But employees should be able to increase the productivity of laborin order to what could be done better .Key Word: Produktivitas kerja, Motivasi, Pegawai Negeri Sipil